Confirmatory Factor Analysis of Strategic Leadership Model of Islamic Private School Administrators in Three Southern Provinces - Abdulwahab, Basel; Suwanmanee, Sinchai; Vehachart, Rungchatchadaporn; Wannapairo, Suntaree (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2022)
This research aimed to validate the consistency of the strategic leadership model of Islamic private schools’ administrators in the three border provinces with empirical data. 278 out of 984 administrators of Islamic private schools in the three border provinces were drawn as a sample group based on the guidelines of Krejcie and Morgan and were randomly stratified according to the size of the schools and then were simply drawn using lottery technique. The instrument used in the research was a 5-scale questionnaire with its validity between .05 and 1 and its reliability value of .979. Data were analyzed using SPSS and LISREL programs. The results of the research showed that the strategic leadership model of Islamic private schools’ administrators in the three southern border provinces including core components and subcomponents were consistent with the empirical data. The second confirmatory component analysis showed that the Chi-Square(χ²) equals 317.58; the degrees of freedom (df) equals 151 index; the level of Goodness of Fit Index (GFI) and the level of Adjusted Goodness of Fit Index (AFGI) were 0.90 0.86, respectively; Standard Root Mean Square Residual (SRMR) was 0.0091; and Root Mean Square Error of Approximation (RMSEA) was 0.063. In addition, the significance of core components included as follows: Strategy Formulation (L=1.00) Strategy Implementation (L=0.94) Strategy Control and Assessment (L=0.94) High Thinking Process (L=0.83) Organizational Direction Setting (L=0.81), respectively.